Balance Exercise Improves Muscle Strength And Body Stability In Frail Older People - Silvia Malasari; Sutriani Sutriani; Andi Masyitha Irwan (Journal of Nursing Care, 2022)
Background: Many elderly people in Indonesia experience falling every year and the half had fallen more than once. This falls due to loss of bone and muscle mass which results in poor of balance. This study aimed to show whether balance excercise could improve muscle strength and balance on elderly people with risk of falling. Methods: This was a quasi-experimental design with two-group pretest-posttest control group. The sample was taken by purposive sampling and the total of 27 elderly people was selected into 2 groups: intervention (n = 14) and control (n = 13). The intervention group received the balance exercise regularly 3 times a week for 3 weeks. The balance exercise consists of plantar flexion, knee flexion, hip flexion, hip extention, and single leg side. Results: As an independent t test showed a significant difference in the balance and muscle strength between the intervention and the control group. Paired t-test on balance values obtained (p = 0.003) and the muscular strength (p = 0.000) which means that there was effect of balance exercise on muscle strength and balance in elderly with risk of falling. Conclusions: Balance exercise for 3 weeks regularly could improve balance score and muscle strength on the older people. Therefore, elderly people escpecially who are at risk of falling better to do balance exercise as their routine and getting support for doing this from family and health workers.